Feminism, Foucault, and embodied subjectivity - McLaren, Margaret A., 1960- (SUNY series in contemporary continental philosophy., 2002)
"Addressing central questions in the debate about Foucault's usefulness for politics, including his rejection of universal norms, his conception of power and power-knowledge, his seemingly contradictory position on subjectivity and his resistance to using identity as a political category, McLaren argues that Foucault employs a conception of embodied subjectivity that is well-suited for feminism. She applies Foucault's notion of practices of the self to contemporary feminist practices, such as consciousness-raising and autobiography, and concludes that the connection between self-transformation and social transformation that Foucault theorizes as the connection between subjectivity and institutional and social norms is crucial for contemporary feminist theory and politics."--Jacket